Cerebral Regulation in Different Maximal Aerobic Exercise Modes - Pires, Flávio O.; dos Anjos, Carlos A. S.; Covolan, Roberto J. M.; Pinheiro, Fabiano A.; St Clair Gibson, Alan; Noakes, Timothy D.; Magalhães, Fernando H.; Ugrinowitsch, Carlos (Frontiers in Physiology, 2016)
ABSTRACT We investigated cerebral responses, simultaneously with peripheral and ratings of perceived exertion (RPE) responses, during different VO2MAX-matched aerobic exercise modes. Nine cyclists (VO2MAX of 57.5 ± 6.2 ml·kg-1·min-1) performed a maximal, controlled-pace incremental test (MIT) and a self-paced 4 km time trial (TT4km). Measures of cerebral (COX) and muscular (MOX) oxygenation were assessed throughout the exercises by changes in oxy- (O2Hb) and deoxy-hemoglobin (HHb) concentrations over the prefrontal cortex (PFC) and vastus lateralis (VL) muscle, respectively. Primary motor cortex (PMC) electroencephalography (EEG), VL and rectus femoris EMG were also assessed throughout the trials, together with power output and cardiopulmonary responses. The RPE was obtained at regular intervals. Similar motor output (EMG and power output) occurred from 70% of the duration in MIT and TT4km, despite the greater motor output, muscle deoxygenation (↓ MOX) and cardiopulmonary responses in TT4km before that point. Regarding cerebral responses, there was a lower COX (↓ O2Hb concentrations in PFC) at 20%, 30%, 40%, 50% and 60%, but greater at 100% of the TT4km duration when compared to MIT. The alpha wave EEG in PMC remained constant throughout the exercise modes, with greater values in TT4km. The RPE was maximal at the endpoint in both exercises, but it increased slower in TT4km than in MIT. Results showed that similar motor output and effort tolerance were attained at the closing stages of different VO2MAX-matched aerobic exercises, although the different disturbance until that point. Regardless of different COX responses during most of the exercises duration, activation in PMC was preserved throughout the exercises, suggesting that these responses may be part of a centrally-coordinated exercise regulation.